PENGARUH VARIABEL KEPUASAN, KEPERCAYAAN, DAN KOMITMEN AFEKTIF TERHADAP PERPINDAHAN NASABAH DI SURABAYA - Andri Rachmad Setiawan; Aniek Maschudah Ilfitriah (STIE Perbanas Surabaya, 2012)
It is a fact that banking services industry is certainly difficult to determine because of the quality of the product which is naturally intangible. In general, customers need the creation is sustainable. Yet, it is not an easy task for us because changes can occur at any time, whether the change in customers tastes or psychological aspects also followed by the changes in environmental conditions that affect aspects of their psychological, social and cultural backgrounds. This study was conducted at Bank BCA Surabaya whose objectives as the following: such as to analyze (1) the effect of affective commitment to customer satisfaction. (2) the influence of trust on affective commitment toward customers. (3) the effect of affictive commitment toward customer migration intentions, It employed 100 respondents, gathered based on nonprobability sampling or convenience sampling. The analysis technique used is multiple linear regression analysis using t-test. The results showed such as (1) satisfaction variables significantly influence the affective commitment variable, while the trust variable does not significantly influence affective commitment variable. (2) variable effective commitment significantly influences the intention variable, displacement variable customer satisfaction, and trust, while no significant effect on the intention variable displacement of cus tomers.